SOCIO-COMMUNICATIVE NATURE OF SCIENTIFIC ACTIVITY - Elena A. Sergodeeva (Вестник Северо-Кавказского федерального университета, 2022)
The item shows socio-communicative basics of the modern scientific activity. There is proof offered to the idea that sociological views on scientific communications allow rethinking the traditional epistemological ideas regarding scientific subjectivity through employing the terms COLLECTIVE SUBJECT and THINKING COLLECTIVE.